A Study to Assess the Effectiveness of Emotional Freedom Techniques on Anxiety Among Wives of Alcoholics - S Jameela; Kristo S. Thapa (Wolters Kluwer Medknow Publications, 2024)
Background: Anxiety is an unpleasant feeling that is typically associated with uneasiness, fear, or worry. It is a normal human emotion that everyone experiences at times many people feel anxious or nervous, when faced with a problem at work, before making an important decision. Anxiety in extreme form, may cause distress which interferes with a person's ability to lead a normal life. Aims: This Study aims is to assess the effectiveness of Emotional Freedom Techniques on Anxiety Among Wives of Alcoholics Method: A quasi-experimental nonequivalent research design with a nonprobability sampling technique was used to conduct a study among 30 wives of alcoholic patients. A generalized anxiety disorder scale (7-point scale) was used to assess the level of anxiety among alcoholic wives. Confidentiality was maintained throughout the research. The data were analyzed by using descriptive statistics and inferential statistics. Result: The result shows that in the pretest, 70 (70%) had no anxiety, 12 (12%) had mild anxiety, and 18 (18%) had moderate anxiety whereas in the post-test, 85 (85%) had no anxiety, 13 (13%) had mild anxiety, and 2 (2%) had moderate anxiety among wives of alcoholics. Conclusion: This study revealed that among wives of alcoholics, a significant proportion had anxiety about the alcoholic spouse by Emotional freedom techniques.